Changes of Bone Turnover Markers in Long Bone Nonunions Treated with a Regenerative Approach. (20th June 2017) - Granchi, Donatella; Gómez-Barrena, Enrique; Rojewski, Markus; Rosset, Philippe; Layrolle, Pierre; Spazzoli, Benedetta; Donati, Davide Maria; Ciapetti, Gabriela
Abstract : In this clinical trial, we investigated if biochemical bone turnover markers (BTM) changed according to the progression of bone healing induced by autologous expanded MSC combined with a biphasic calcium phosphate in patients with delayed union or nonunion of long bone fractures. Bone formation markers, bone resorption markers, and osteoclast regulatory proteins were measured by enzymatic immunoassay before surgery and after 6, 12, and 24 weeks. A satisfactory bone healing was obtained in 23 out of 24 patients. Nine subjects reached a good consolidation already at 12 weeks, and they were considered as the "early consolidation" group. We found that bone-specific alkaline phosphatase (BAP), C-terminal propeptide of type I procollagen (PICP), and beta crosslaps collagen (CTX) changed after the regenerative treatment, BAP and CTX correlated to the imaging results collected at 12 and 24 weeks, and BAP variation along the healing course differed in patients who had an "early consolidation." A remarkable decrease in BAP and PICP was observed at all time points in a single patient who experienced a treatment failure, but the predictive value of BTM changes cannot be determined. Our findings suggest that BTM are promising tools for monitoring cell therapy efficacy in bone nonunions, but studies with larger patient numbers are required to confirm these preliminary results.